Tingkat Kepuasan Masyarakat Terhadap Pendaftaran Online Pada Aplikasi Mobile JKN - Herlinawati; Lilis Banowati; Devi Revilia (HEALTH CARE : JURNAL KESEHATAN, 2021)
The COVID-19 pandemic which occurs in all countries including Indonesia has forced Administrative Body for Health (BPJS) to adapt to new service patterns that continuously pay attention to health protocols without reducing the quality of service that has been running well. Mobile National Health Insurance (JKN) is one of the most effective alternatives that BPJS can currently use to continue its services in the current condition. This study aims to determine the level of community satisfaction with BPJS online registration on the mobile JKN application during the COVID-19 Pandemic. This was a descriptive study. The population was all BPJS participants in Cirebon District in 2021 who have downloaded the JKN mobile application as many as 129,357 participants. Determination of sample size used the Slovin formula which obtained 100 respondents taken by accidental sampling technique. Data were analyzed using univariate analysis in the form of a percentage. The results showed that most respondents (73%) were satisfied with the BPJS online registration on the Mobile JKN application during the COVID-19 pandemic. It is expected that Administrative Body for Health of Cirebon District Branch will conduct socialization and demonstrations through print, electronic and radio media to be more intensified regarding the use of the Mobile JKN application.